The Need for Monitoring and Assessment of Legal Aid Quality in South Africa - Holness, Dave (Potchefstroom Electronic Law Journal, 2022)
Legal aid is needed in South Africa as one mechanism for poor South Africans to realise their legal rights and to use the law as a vehicle for positive social change in a grossly unequal society in which deep poverty is rife. However, simply having a legal aid service provider is insufficient if the quality of such services is not satisfactory. But how can high quality legal services be ensured? This paper considers how different forms of legal aid service provision can be effectively monitored and assessed to ensure that satisfactory standards of legal aid work are delivered. Categories of "legal aid" (broadly construed) which are considered are legal NGOs, including university law clinics, the state’s Legal Aid South Africa telephonic advice, and pro bono work by private lawyers. Separate research has focussed on the need for much improved coordination between legal service providers to promote co-operation among legal aid services. The next step is to ensure that such coordination leads to quality services and promoting quality control mechanisms which are appropriate and which can be considered best practice. This paper analyses and discusses this next step. If legal aid is not of an adequate standard or quality assurance is not in place, the legal aid is not serving a positive function. The paper considers viable means for vetting the quality of these free legal services in a South African context, including telephonic legal advice in the Covid era. It suggests mechanisms to promote high-level free legal service provision by assessing the quality of such services. Legal aid quality control methods abroad were analysed to serve as an indicator of the options used in this regard in those jurisdictions. The question to be answered is what quality control measures are most apposite in the South African legal aid arena.